Rhizobia and non-rhizobial nodule bacteria with ACC deaminase increase both nodulation and stress resistance - Gamalero, Elisa; Glick, Bernard R. (Frontiers in Microbiology, 2025)
Strains of Rhizobia that possess the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase facilitate the nodulation of cognate legume hosts. Some rhizobial strains that contain ACC deaminase also help plants to overcome some types of environmental stress including heat, salt, drought and the presence of heavy metals. In addition, non-rhizobial strains of bacteria isolated from legume nodules that contain ACC deaminase increase the extent of rhizobia nodulation and the resistance of the legume to environmental stresses. Here, the literature addressing the role of ACC deaminase in increasing legume nodulation and protecting plants against a range of environmental stresses is summarized and discussed.